The Profile of Yeast Growth During Very High Gravity Ethanol Fermentation Under Batch and Fed-batch System - S. Jasrey, Max Suil (Universiti Malaysia Sarawak (UNIMAS), 2018)
Very high gravity (VHG) fermentation techonology uses high concentration of sugar. The minimum amount of sugar use in VHG fermentation techonology is 270 g/L. Under VHG fermentation, both fermentation rate and ethanol concentration can be increased. However, during VHG ethanol fermentation, the yeast cell encounter an osmotic pressure. Besides that, the consumption of substrate and accumulation of ethanol product during fermentation will inhibit the yeast propagation which result in cell death and incomplete sugar utilization. Thus, in this study, the yeast growth profile (YGP) under batch and fed-batch fermentation system were analyzed during VHG fermentation condition. Based on the YGP of batch system, the pre-determined time for addition of fresh substrate to the fed-batch system was at 36 fermenting hour. The rate of ethanol production and yeast growth increase under fed-batch fermentation. The highest concentration of ethanol produce under batch system is 134.21 g/L at 84 fermenting hour while I 12.72 g/L at 36 fermenting hour for fed-batch system. Based on the results of the yeast growth profile, fed-batch system able to dilute the formation of exo-metabolite during fermentation and prolonged the yeast growth until 72 fermenting hours.